Ubiquitin Carboxyl-Terminal Hydrolase L1 of Cardiomyocytes Promotes Macroautophagy and Proteostasis and Protects Against Post-myocardial Infarction Cardiac Remodeling and Heart Failure - Wu, Penglong; Li, Yifan; Cai, Mingqi; Ye, Bo; Geng, Bingchuan; Li, Faqian; Zhu, Hua; Liu, Jinbao; Wang, Xuejun (Frontiers in Cardiovascular Medicine, 2022)
Ubiquitin carboxyl-terminal hydrolase L1 (UCHL1) is a deubiquitinase known to play essential roles in the nervous tissue. Myocardial upregulation of UCHL1 was observed in human dilated cardiomyopathy and several animal models of heart disease, but the (patho)physiological significance of UCHL1 in cardiomyocytes remains undefined. Hence, we conducted this study to fill this critical gap. We produced cardiomyocyte-restricted Uchl1 knockout (CKO) by coupling the Uchl1-floxed allele with transgenic Myh6-Cre in C57B/6J inbred mice. Mice transgenic for Myh6-Cre were used as controls (CTL). Myocardial Uchl1 proteins were markedly reduced in CKO mice but they did not display discernible abnormal phenotype. Ten-week old CTL or CKO mice were subjected to left anterior descending artery ligation (myocardial infarction, MI) or sham surgery (Sham) and characterized at 7- and 28-day after surgery. Compared with Sham mice, significant increases in myocardial UCHL1 proteins were detected in CTL MI but not in CKO MI mice. MI-induced left ventricular (LV) chamber dilation, reduction of ejection fraction (EF) and fractional shortening (FS), and LV anterior wall thinning detected by echocardiography were comparable between the CTL MI and CKO MI groups 7-day post-MI. However, by 28-day post-MI, MI-induced LV chamber dilatation, EF and FS reduction, increases of myocardial ubiquitin conjugates, and increases in the heart weight to body weight ratio and the ventricular weight to body weight ratio were significantly more pronounced in CKO MI than CTL MI mice. As further revealed by LV pressure-volume relationship analyses, CKO MI mice but not CTL MI mice displayed significant decreases in stroke volume, cardiac output, and the maximum rates of LV pressure rising or declining and of LV volume declining, as well as significant increases in LV end-diastolic pressure and Tau, compared with their respective Sham controls. LC3-II flux assays reveal that autophagic flux is decreased in CKO mouse myocardium as well as in cultured Uchl1-deficient cardiomyocytes. In conclusion, UCHL1 of cardiomyocytes is dispensable for development but promotes macroautophagy in cardiomyocytes. Upregulation of UCHL1 in post-MI hearts occurs primarily in the cardiomyocytes and protects against post-MI cardiac remodeling and malfunction likely through supporting autophagic flux and proteostasis during a stress condition.